2018
DOI: 10.1021/acsenergylett.8b00515
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Vacancies Boost Reconstruction in Nickel Hydroxide Electrocatalyst

Abstract: Because the reconstruction of catalysts is generally observed during oxidation reactions, understanding the intrinsic structure-related reconstruction ability of electrocatalysts is highly desirable but challenging. Herein, a controllable hydrolysis strategy is developed to obtain nickel hydroxide electrocatalysts with controllable nickel vacancy (V Ni ) concentrations, as confirmed by advanced spectroscopic characterization. Electrochemical measurements show that the reconstruction can be promoted with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
171
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(185 citation statements)
references
References 45 publications
(92 reference statements)
7
171
0
Order By: Relevance
“…NiOOH OEC was basally reported to show fast water oxidation kinetics than FeOOH . However, deposition of NiOOH on BiVO 4 always generated a relatively low photocurrent for water oxidation compared with BiVO 4 /FeOOH, because of the more substantial interface recombination at the BiVO 4 /NiOOH .…”
Section: Figurementioning
confidence: 99%
“…NiOOH OEC was basally reported to show fast water oxidation kinetics than FeOOH . However, deposition of NiOOH on BiVO 4 always generated a relatively low photocurrent for water oxidation compared with BiVO 4 /FeOOH, because of the more substantial interface recombination at the BiVO 4 /NiOOH .…”
Section: Figurementioning
confidence: 99%
“…EPR results showed that the Ni 3+ signal in V‐Ni(OH) 2 ‐Ru was stronger than that in V‐Ni(OH) 2 , which demonstrated the existence of more Ni 3+ (Figure S3a, Supporting Information). This was probably from the considerable electronic coupling in the interfaces . By contrast, P‐Ni(OH) 2 ‐Ru showed almost unchanged EPR signal relative to P‐Ni(OH) 2 (Figure S3b, Supporting Information).…”
mentioning
confidence: 99%
“…The abundant nickel vacancies in V‐Ni(OH) 2 have been proved to be vital in achieving single‐atom Ru incorporation with high‐density. As a reference, Ni(OH) 2 with fewer nickel vacancies was prepared and treated with Ru cations as V‐Ni(OH) 2 ‐Ru (namely, P‐Ni(OH) 2 and P‐Ni(OH) 2 ‐Ru, respectively, see the Experimental Section) . A very low Ru/Ni ratio (0.08 wt%) has obtained for P‐Ni(OH) 2 ‐Ru (Table S1, Supporting Information).…”
mentioning
confidence: 99%
“…However, until now, little attention has been paid on the study of the surface evolution of the transition‐metal‐based electrocatalysts to uncover the real active sites for OER. Since the electrocatalytic oxygen evolution takes place on the surface layer of the catalyst, and the electrocatalytic properties are related closely with the surface electronic structure of the catalysts, including the adsorption barriers of the intermediates and the entire charge transportation, further understanding of the surface evolution and electronic structure of transition‐metal‐based catalysts during oxygen evolution is necessary to better design the highly‐efficient OER electrocatalysts …”
Section: Introductionmentioning
confidence: 99%